Critical Thinking and the Challenges of Internet - Plencner, Alexander (Communication Today, 2014)
In this article, the author addresses some challenges to information searches and information evaluation which were brought by the Internet. Large segments of audience are exaggerating their awareness and do not realize that their online behavior is driven more by emotions than by critical assessment of primary sources. The result is growing popularity of conspiracy theories, pseudoscience, propaganda, and alternative medicine. These are all examples of biased reasoning. Due to scientists, scholars, teachers, and journalists, this trend can be considered as a potential threat to public health and democracy. Publics incapable of informed choices can be manipulated to support radical political utopia or to reject evidence based treatments. Some basic principles of media literacy, scientific literacy and critical thinking are outlined. They can be used as tools for raising awareness, enhancing reasoning and adopting more objective perspective. This article is based on assumption that behind irrational beliefs there often lies anxiety, precondition for distrust derived from childhood. Not only general users of the Internet tend to overestimate their competence in domains of their interest (so called Dunning-Kruger effect), their behavior may be affected by unrecognized emotional agenda (cautious monitoring of environment for danger, suspicious attitude towards authority figures and official sources of information). The article is enclosed with some recommendation how to evaluate information sources on the Internet and how to be more empathetic in online discussions in order to inspire to reasonable and healthy choices.